The effect of varying cutting speeds on tool wear during conventional and Ultrasonic Assisted Drilling (UAD) of Carbon Fibre Composite (CFC) and titanium alloy stacks - Dahnel, Aishah Najiah; Ascroft, Helen; Barnes, Stuart (Elsevier, 2016)
The application of Carbon Fibre Composite (CFC) and titanium alloys are becoming more prevalent in aerospace industry due to their high-strength-to-weight ratio. However, the drawback of these materials is poor machinability. This paper presents the potential of Ultrasonic Assisted Drilling (UAD) of CFC and titanium Ti6Al4V stacks in delaying tool wear progression. Experiments comparing conventional and UAD were conducted using 6.1 mm diameter tungsten carbide drills, employing constant feed rate of 0.05 mm/rev and cutting speeds of 25, 50 and 75 m/min, demonstrated that the drills used in UAD underwent lower tool wear rate and thrust forces than conventional drilling.